A systematic review on the effectiveness of acceptance and commitment therapy on academic procrastination - Sook Huey Lee; Azizah Othman; Fatanah Ramlee (Discover Psychology)
Abstract Background Academic procrastination is characterized by the habitual delay of academic tasks and is a widespread issue among students. This systematic review aims to examine the application of Acceptance and Commitment Therapy (ACT) in reducing academic procrastination among students. Materials and methods Studies were included if they used ACT to address academic procrastination. Non-English papers were excluded. A systematic literature search was conducted using PubMed, the Cochrane Controlled Trials Register, Google Scholar, ScienceDirect, and EBSCOhost, Scopus and Web of Science. Keywords included (“Acceptance and Commitment Therapy” OR “ACT”) AND “academic procrastination.” Data were extracted and analyzed to assess study design, intervention components, outcomes, and the quality of evidence on ACT for academic procrastination. Results Nine empirical studies met the inclusion criteria. The findings indicated that ACT improved core processes of psychological flexibility, including values, mindfulness, and committed action. Positive outcomes across cohort studies support the effectiveness of ACT, with evidence rated at level 2 A. Conclusion ACT appears to be a promising intervention for reducing academic procrastination by enhancing psychological flexibility. However, clinicians should integrate these findings with individual student preferences and contexts. More rigourous randomized controlled trials are needed to explore underlying mechanisms and determine the optimal dosage of intervention.